Reuse of Spent Foundry Sand in Development of Glass-Ceramic Material with Wollastonite Phase - Da Silva Magalhães, Renata [UNESP]; Dos Santos, Luis Fernando [UNESP]; De Almeida Santos, Gleyson Tadeu [UNESP]; Pereira, Luiz Augusto Stuani; Fernandes, José Diego [UNESP]; De Souza Albas, Agda Eunice [UNESP]; Teixeira, Silvio Rainho [UNESP] (FapUNIFESP (SciELO), 2023)
Spent Foundry Sand is one of the largest industrial solid wastes generated by foundries in the production of iron and steel components. Currently, millions of tons of molten sands are discarded worldwide. Therefore, this work aims to reuse the Spent Foundry Sand for the production of glass-ceramic materials, since this reuse minimizes the environmental impacts related to its discarding. The Spent Foundry Sand, composed of 60% SiO2, was mixed with limestone and melted at 1500 C to produce the glass (melting and rapid cooling method). The materials were characterized by X-Ray Fluorescence, X-Ray Diffraction and thermal analysis. The X-Ray Diffraction results of the glass tablets treated at 875, 941 and 1050 C show that the formed phases are Wollastonite-1A, β-Wollastonite and Akermanite. In summary, it is possible to produce glass-ceramic from Spent Foundry Sand with Wollastonite phase.
Keywords: Glass Ceramic; Spent Foundry Sandy; Wollastonite.